A scoping review of mentorship in Graduate Medical Education: a proposed conceptual framework - Abdelmannan, Dima; Buhumaid, Rasha; Salman, Hira; Ba Madhaf, Wail A. Abdulrahman Hasan; AlRajaby, Hafidh Mohammad Khamis; Zary, Nabil; Guraya, Shaista Salman (Frontiers in Medicine, 2025)
IntroductionMentorship is increasingly recognized as a foundational stone within Graduate Medical Education (GME), contributing to clinical competency, scholarly engagement, professional identity formation, and psychological well-being. Despite its growing recognition, mentorship in GME remains inconsistently structured, under-theorized, and variably evaluated. This conceptual and structural ambiguity hampers the ability to design, compare, and scale mentorship efforts meaningfully across settings. This scoping review aimed to systematically explore the structure, theoretical foundations, evaluation approaches, and reported outcomes of mentorship programs in GME, and to develop a conceptual framework to guide the design of context-sensitive, outcome-aligned mentorship interventions.MethodsThe scoping review followed Arksey and O’Malley’s five-stage methodology and the findings were reported according to PRISMA-ScR guidelines. A comprehensive search of PubMed, Scopus, CINAHL, and Embase was conducted in January 2025, covering studies published between 2015 and 2025. Eligibility was defined using the Population–Concept–Context framework. Data were extracted using a structured template and synthesized thematically.ResultsA total of 94 studies were included. Mentorship programs varied widely in structure, with formal, informal, peer, and near-peer models observed. Only 27 studies reported use of theoretical frameworks, and evaluation approaches were often limited to non-validated tools and descriptive outcomes. Four main analytical clusters emerged: program structure, theoretical/conceptual frameworks, evaluation approaches, and reported outcomes. Outcomes commonly reported included career development, academic productivity, clinical competency, leadership, well-being, and professional growth. However, the main highlight was a lack of theoretical underpinnings, standardized outcome measurement and mentor training. Cultural responsiveness and equity were rarely considered in mentorship programs.ConclusionThis scoping review highlights the need for mentorship programs in GME to be more systematically designed, theory-informed, and rigorously evaluated. Key gaps include the underutilization of conceptual models, the lack of validated evaluation tools, and insufficient attention to mentor training and equity considerations. Building on the findings of this scoping review, we propose a conceptual framework that aligns mentorship models with learner level, skill focus, and mentoring format across psychological and sociological domains. This framework is intended to guide the development of robust, context-sensitive, and theory-informed mentorship programs with measurable outcomes, ultimately fostering sustainable mentorship cultures that enhance learner development and improve healthcare practice in Graduate Medical Education (GME).